Wisata Virtual Ala’ Novel Habiburrahman El Shirazy - Pramono, Dedi (Bahasa: Jurnal Keilmuan Pendidikan Bahasa dan Sastra Indonesia, 2022)
The strength of the concept of "tourism" lies in its uniqueness and uniqueness of objects from existing places/situations/views. Likewise in virtual tourism in verbal form, for example in novels. The type of tourism, virtual tourism contained in the novel includes recreational tourism and cultural tourism. Many have acknowledged that the strength of Habiburrahman's novels lies in their ability to describe objects of place/time/situation in a unique way, at least different from the objects of place/time/situation that was usually described by their predecessors. This article aims to discuss the model of tourist objects described by Habiburrahman in his novel, both related to the object model in recreational tourism and cultural tourism, which can become a virtual tourist vehicle for readers. The study was conducted using a descriptive method that emphasized content. The object of this study focuses on two novels by Habiburrahman El Shirazy, namely Ayat-ayat Cinta (2004) with a formal object on the verbal construction of virtual tourism images. The virtual tourism featured in Habiburrahman El Shirazy's novel appears in the type of recreational tourism including places and culinary objects and culinary themes. Cultural tourism includes objects of customs, objects of scientific tradition, and transportation traditions. Objects are described carefully with the support of the use of associational language styles, hyperbole, climax, and rhetoric so as to be able to position the reader as if they are really present in the middle of the objects and events in the novel's story. AbstrakKekuatan konsepsi “wisata’  terletak pada kekhasannya dan keunikan objek dari tempat/ situasi/tampilan yang sudah ada. Demikian juga dalam wisata virtual dalam ujud verbal, misalnya di dalam novel. Dalam penjenisan wisata, wisata virtual yang terdapat pada novel meliputi wisata rekreasi dan wisata budaya. Telah banyak yang mengakui bahwa kekuatan novel-novel  Habiburrahman terletak pada kemampuannya menggambarkan objek-objek  tempat/waktu/situasi secara khas, paling tidak berbeda dengan objek tempat/waktu/situasi yang biasa digambarkan para pengarang pendahulunya. Artikel ini bertujuan membahas model objek-objek wisata yang digambarkan  Habiburrahman di dalam novelnya, baik berkaitan dengan model objek pada jenis wisata rekreasi maupun pada wisata budaya,  yang mampu menjadi wahana wisata virtual bagi pembaca. Kajian dilakukan dengan menggunakan metode deskriptif yang ditekankan pada content. Objek material kajian ini berfokus pada dua novel karya Habiburrahman El Shirazy yaitu Ayat-ayat Cinta (2004) dengan objek formal pada konstruksi verbal gambaran wisata virtual. Wisata virtual yang ditampilkan dalam novel Habiburrahman El Shirazy tampil pada jenis wisata  rekreasi meliputi  objek tempat dan objek kuliner dan temat kuliner Pada jenis wisata budaya meliputi objek adat istiadat, objek tradisi keilmuan dan tradisi transportasi. Objek digambarkan secara cermat dengan dukungan pemakaian gaya bahasa asosiasi, hiperbola, klimaks, dan retorika sehingga mampu memposisikan pembaca seakan benar-benar hadir di tengah objek dan peristiwa pada cerita novel tersebut.